Skill, Innovation and Wage Inequality: Can Immigrants be the Trump Card? - Gouranga Gopal Das; Sugata Marjit; Mausumi Kar (Center for Economic Studies and ifo Institute (CESifo), 2019)
With the ensuing immigration reform in the US, the paper shows that targeted skilled immigration into the R&D sector that helps low-skilled labor is conducive for controlling inequality and raising wage. Skilled talent-led innovation could have spillover benefits for the unskilled sector while immigration into the production sector will always reduce wage, aggravating wage inequality. In essence, we infer: (i) if R&D inputs contributes only to skilled sector, wage inequality increases in general; (ii) for wage gap to decrease, R&D sector must produce inputs that goes into unskilled manufacturing sector; (iii) even with two types of specific R&D inputs entering into the skilled and unskilled sectors separately, unskilled labor is not always benefited by high skilled migrants into R&D-sector. Rather, it depends on the importance of migrants' skill in R&D activities and intensity of inputs. Inclusive immigration policy requires inter-sectoral diffusion of ideas embedded in talented immigrants targeted for innovation. Empirical verification using a VAR regression model in the context of the USA confirms the conjectures, and the empirical results substantiates our policy-guided hypothesis that skilled immigration facilitates innovation with favorable impact on reducing wage-gap.
Keywords: F22; J31; O15; 330; H1B; immigration; innovation; wage gap; skill; R&D; policy; RAISE Act; VAR